Classroom Management and Social Environment in Students’ Academic Achievement: A Literature Review - Maulana, Meiviani Nurul Aisyah; Maulana, Meiviana Nurul Khadijah; Tarsono, Tarsono (Jurnal Psikologi Teori dan Terapan, 2026)
Background: Low academic achievement among elementary school students often linked to ineffective classroom management and unfavorable social environments. These factors are frequently examined in isolation, resulting in a fragmented understanding of their combined influence on learning outcomes. Objective: This study aims to synthesize existing literature to examine the integrated role of classroom management and social environment dynamics in shaping students’ academic achievement. Method: This research employed a qualitative literature review method by analyzing peer-reviewed journal articles, academic books, and scholarly reports related to classroom management, peer interactions, bullying, and academic achievement in elementary education. Data were analyzed to identify recurring concepts and relationships across studies. Results: The findings indicate effective classroom management with structured instruction, positive teacher student relationships, and clear routines enhances academic engagement, while supportive social environments foster emotional well-being and learning motivation. In contrast, negative peer interactions consistently undermine students’ academic outcomes. Conclusion: Classroom management and social environment function as an interconnected system influencing academic achievement, underscoring the importance of integrating instructional and social strategies in elementary education practice and policy. Abstrak Latar Belakang: Rendahnya prestasi akademik pada siswa sekolah dasar sering dikaitkan dengan pengelolaan kelas yang kurang efektif serta lingkungan sosial yang tidak kondusif. Faktor-faktor tersebut kerap dikaji secara terpisah sehingga menghasilkan pemahaman yang terfragmentasi mengenai pengaruh gabungannya. Tujuan: Penelitian ini bertujuan untuk mensintesis literatur guna mengkaji peran terpadu pengelolaan kelas dan dinamika lingkungan sosial dalam membentuk prestasi akademik siswa. Metode: Penelitian ini menggunakan metode kajian pustaka kualitatif dengan menganalisis artikel jurnal bereputasi, buku akademik, dan laporan ilmiah yang berkaitan dengan pengelolaan kelas, interaksi teman sebaya, perundungan, serta prestasi akademik pada pendidikan dasar. Data dianalisis menggunakan sintesis tematik untuk mengidentifikasi konsep dan hubungan yang berulang antar penelitian. Hasil: Temuan menunjukkan pengelolaan kelas yang efektif dengan pembelajaran yang terstruktur, hubungan guru–siswa yang positif, dan rutinitas yang jelas, mampu meningkatkan keterlibatan akademik, serta lingkungan sosial yang suportif mendukung kesejahteraan emosional dan motivasi belajar. Sebaliknya, interaksi negatif antar teman sebaya menurunkan capaian akademik siswa. Kesimpulan: Pengelolaan kelas dan lingkungan sosial memengaruhi prestasi akademik, sehingga menegaskan pentingnya integrasi strategi instruksional dan sosial dalam praktik serta kebijakan pendidikan dasar.